2015
DOI: 10.1159/000437203
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Trial of Low-Flow Oxygen versus Nasal Continuous Positive Airway Pressure in Preterm Infants

Abstract: Background: Nasal continuous positive airway pressure (nCPAP) stabilizes the residual volume and may decrease the risk of ‘atelectotrauma', potentially promoting lung development in neonates. Objectives: To assess whether replacing nCPAP by low-flow O2 by nasal cannula affects lung function expressed as the arterial/alveolar oxygen tension ratio (a/A pO2 ratio) on postnatal day 28. Methods: Preterm infants (birth weight <1,500 g and gestational age, GA >26 + 0 weeks) stable on nCPAP betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…As a result, work of breathing (WOB) is often increased and gas exchange impaired 1. In an attempt to restore lung function and reduce WOB, preterm infants often receive respiratory support with nasal continuous positive airway pressure (nCPAP) and/or low flow nasal cannula (LFNC) as the most frequently used modes 2 3…”
Section: Introductionmentioning
confidence: 99%
“…As a result, work of breathing (WOB) is often increased and gas exchange impaired 1. In an attempt to restore lung function and reduce WOB, preterm infants often receive respiratory support with nasal continuous positive airway pressure (nCPAP) and/or low flow nasal cannula (LFNC) as the most frequently used modes 2 3…”
Section: Introductionmentioning
confidence: 99%
“…However, our results differ from those described by Abdel-Hady et al 8 in 60 infants with a GA of !28 weeks who received CPAP 5 cm H 2 O with FiO 2 0.3 and who were weaned either from CPAP directly or by nasal cannula (2 lpm). In this study, the nasal cannula group spent more time on respiratory support and with supplemental oxygen (18 [11.5-29] days vs. 10.5 [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] days; p ¼ 0.003). It should be noted that the flow rate in this study was lower than in our study and the characteristics of the study population were different (mean GA 31 weeks and mean BW 1,600 g).…”
Section: Discussionmentioning
confidence: 78%
“…Parental perception of infant comfort was also significantly higher in the nHFT group (median 25 [23][24][25][26][27] vs. 20 [15][16][17][18][19][20][21][22][23]; p ¼ 0.0004) There were no differences in morbidities or related complications (►Table 2). There were no differences in the results between both approaches when patients were stratified according to gestational age.…”
Section: Resultsmentioning
confidence: 99%
“…Oxygen therapy is the administration of oxygen at higher concentrations than ambient air (20.9%) for combating hypoxia (Fulmer & Snider, ). Previous studies (Heiring, Steensberg, Bjerager, & Greisen, ; Ringbaek, Viskum, & Lange, ) have revealed that long‐term and low‐flow oxygen administration in some chronic diseases (such as chronic obstructive pulmonary disease) can not only improve hypoxia symptoms but also reduce the length of hospital stay and prolong life expectancy. Nasal cannulas are the most widely used tool for oxygen administration in hospital and community; the oxygen delivered by nasal cannulas may or may not be humidified by humidifier bottles.…”
Section: Introductionmentioning
confidence: 99%